Meningkatkan Kesadaran Masyarakat Terhadap Hak-Hak Disabilitas Melalui Mini Project Ramah Disabilitas - Sinaga, Binsar Martua Valentino; Sianturi, Chintya Khasanah; Gunawan, Danu; Tarigan, Rachel Br; Panjaitan, Sirana Mikelvania Baby (Yayasan Literasi Sains Indonesia, 2023)
Humans are social beings who crave and desire a healthy and normal life. There are humans who are lucky and should be grateful for being born normally without having any physical or mental disabilities, but there are also humans who are born with both mental and physical disabilities. On the other hand, there are also humans who are born normally and do not have disabilities, but in the course of their lives, there are unintentional accidents that make these humans disabled or disabled. The state is present in protecting and fulfilling the needs of disabilities in various aspects of life. According to Number 8 of 2016 concerning Persons with Disabilities states that persons with disabilities are any person who experiences physical, intellectual, mental and/or sensory limitations for a long time in interacting with the environment may experience obstacles and difficulties to participate fully and effectively with other citizens based on equal rights. The disability-friendly Mini Project aims to increase public awareness and concern for insights about disability such as rights and various public facilities for persons with disabilities. The method used in the disability-friendly mini project includes the stages of preparation, intake and contact, assessment, planning, intervention and program formulation, evaluation and termination.